Well-differentiated G1 and G2 pancreatic neuroendocrine tumors: a meta-analysis of published expanded DNA sequencing data - Andersen, Kirstine Øster; Detlefsen, Sönke; Brusgaard, Klaus; Christesen, Henrik Thybo (Frontiers in Endocrinology, 2024)
Well-differentiated pancreatic neuroendocrine tumors (PNETs) can be non-functional or functional, snd sporadic or hereditary (primarily multiple endocrine neoplasia type 1 (MEN1). In the recent years, reports on genetic somatic events in both sporadic and hereditary PNETs have emerged, providing a basis for a more detailed molecular understanding of the pathophysiology. In this systematic meta-analysis review, we made a collation and statistical analysis of aggregated frequent genetic alterations and potential driver events in human G1/G2 PNETs. A systematic search was performed in concordance with the PRISMA guidelines. A PubMed search for studies using whole exome, whole genome, or targeted gene panel (+400 genes) sequencing of G1/G2 PNETs were conducted on September 23, 2023. Fourteen datasets were included on 225 PNETs, which were divided into subtypes. Further, non-functioning and functioning PNETs were distinguished into two groups for pathway evaluation. The collated genetical analyses were conducted using the 'maftools' R-package. Sporadic PNETs accounted 72.0% (162/225), hereditary PNETs 13.3% (30/225), unknown germline status 14.7% (33/225). The most frequently altered gene was MEN1, with somatic variants and copy number variations in overall 42 % (95/225); hereditary PNETs (germline variations in MEN1, VHL, Formateret: Haevet skrift CHEK2, BRCA2, PTEN, CDKN1B, and/or MUTYH) 57% (16/30); sporadic PNETs 36% (58/162); unknown germline status 64% (21/33). The MEN1 point mutations/indels were distributed throughout MEN1. Overall, DAXX (16%, 37/225) and ATRX-variants (12%, 27/225) were also abundant with missense mutations clustered in mutational hotspots associated with histone binding, and translocase activity, respectively. DAXX mutations occurred more frequently in PNETs with MEN1 mutations, p<0.05. While functioning PNETs shared few variated genes, non-functioning PNETs had more recurrent variations in genes associated with the Phosphoinositide 3-kinase, Wnt, NOTCH, and Receptor Tyrosine Kinase-Ras signaling onco-pathways.In conclusion, the somatic genetic alterations in G1/G2 PNETs are diverse, but with distinct differences between sporadic vs. hereditary, and functional vs. non-functional PNETs. Increased understanding of the genetic alterations may lead to identification of more drivers and driver hotspots in the tumorigenesis in well-differentiated PNETs, potentially giving a basis for new drug targets potentially giving a basis for the identification of new drug targets. (Funded by NNF19OC0057915).